(3GdaSGO h CNdGbjGJ GdYed (B/s - (3HhaGdWI,eMeO Sja GdOjfs ((3GdLRGFQ(B: s (3GdaG ddhKGFb(B, s, 2022)
(3LhgQ GdaSGO h CfhGYg h eXGgQ GdaSGO GdGOGQj h GdeGdj , CSHGH GdaSGO GdEOGQj h GdeGdj h BKGQg , eMGQHI GdaSGO ef WQa GdgjFGJ h GdefXeGJ GdOhdjI h GdeMdjI , WQb YdGL GdaSGO h CHQR GdJLGQH GdOhdjI aj ecGaMJg h CNjQG CNdGbjGJ GdYed(B.s
(3eQGLY U(B.159s
Keywords: (3CNdGbjGJ GdYeds; (3GdaSGO GdGOGQjs